Physical and chemical composition of the must and white wine of grapevine cultivars in response to rootstocks - Silva, Marlon Jocimar Rodrigues da; Tecchio, Marco Antonio; Moura, Mara Fernandes; Brunelli, Luciana Trevisan; Imaizumi, Vitor Massami; Venturini Filho, Waldemar Gastoni (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the influence of the rootstocks 'IAC 766 Campinas' and '106‑8 Mgt Ripária do Traviú' on the physicochemical characteristics of must and wine of the 'IAC 116‑31 Rainha', 'IAC 21‑14 Madalena', and 'BRS Lorena' grapevines. Grape must was evaluated for pH, soluble solids (SS), total acidity (TA), and SS/TA ratio. In wine, the following physicochemical analyses were performed: density, alcohol content; total, volatile, and fixed acidity; pH; dry extract; reducing sugars; reduced dry extract; alcohol in weight/reduced dry extract; free and total sulfur dioxide; total polyphenol index (I 280); total polyphenols; flavonoids; and antioxidant activity. Must characteristics of 'IAC 21‑14 Madalena' were not affected by rootstocks; however, the 'IAC 766 Campinas' rootstock promoted higher SS/TA in 'IAC 116‑31 Rainha' must and lower SS/TA in 'BRS Lorena' must. The 'IAC 766 Campinas' and '106‑8 Mgt Ripária do Traviú' rootstocks influenced pH and alcohol content of 'IAC 116‑31 Rainha' wine, the dry extract of 'IAC 21‑14 Madalena' wine, and the fixed acidity of 'BRS Lorena' wine. There was no influence of the rootstocks on the phenolic compounds and antioxidant activity of wines.